Geological constraints on the dynamic emplacement of cone-sheets – The Ardnamurchan cone-sheet swarm, NW Scotland. (November 2015) - Mathieu, Lucie; Burchardt, Steffi; Troll, Valentin R.; Krumbholz, Michael; Delcamp, Audray
Abstract: Cone-sheets are a significant constituent of many central volcanoes, where they contribute to volcano growth by intrusion and through flank eruptions, although the exact emplacement mechanisms are still controversially discussed. In particular, it is not yet fully resolved whether cone-sheets propagate as magma-driven, opening-mode fractures or as shear fractures, and to what extent pre-existing host-rock structures and different stress fields influence cone-sheet emplacement. To shed further light on the role of these parameters in cone-sheet emplacement, we use detailed field and remote sensing data of the classic Ardnamurchan cone-sheet swarm in NW-Scotland, and we show that the cone-sheets primarily propagated as opening-mode fractures in the σ1–σ2 plane of the volcanic stress field. In addition, more than one third of the Ardnamurchan cone-sheet segments are parallel to lineaments that form a conjugate set of NNW and WNW striking fractures and probably reflect the regional NW–SE orientation of σ1 during emplacement in the Palaeogene. Cone-sheets exploit these lineaments within the NE and SW sectors of the Ardnamurchan central complex, which indicates that the local volcanic stress field dominated during sheet propagation and only allowed exploitation of host-rock discontinuities that were approximately parallel to the sheet propagation path. In addition, outcrop-scale deflections of cone-sheets into sills and back into cone-sheets (also referred to as "staircase" geometry) are explained by the interaction of stresses at the propagating sheet tip with variations in host-rock strength, as well as the influence of sheet-induced strain. As a consequence, cone-sheets associated with sill-like segments propagate as mixed-mode I/II fractures. Hence, cone-sheet emplacement requires a dynamic model that takes into account stress fields at various scales and the way propagating magma interacts with the host rock and its inherent variations in rock strength. Highlights: Ardnamurchan cone-sheets are Mode I fractures following the volcanic stress field. Cone-sheet-sill staircase configurations reflect the local stress-field variations. Cone-sheets exclusively exploited favourably oriented host-rock discontinuities.